The new public management : improving research and policy dialogue - Barzelay, Michael (Aaron Wildavsky forum for public policy, 2001)
How policymakers should guide, manage, and oversee public bureaucracies is a question that lies at the heart of contemporary debates about government and public administration. In their search for better systems of public management, reformers have looked in particular at the United Kingdom, Australia, and New Zealand.